The Swallowing Clinical Assessment Score in Parkinson’s Disease (SCAS-PD) Is a Valid and Low-Cost Tool for Evaluation of Dysphagia: A Gold-Standard Comparison Study - Larissa L. Branco; Sheila Trentin; Carla Helena Augustin Schwanke; Irenio Gomes; Fernanda Loureiro (Journal of Aging Research)
Background. Dysphagia is a predictor of mortality in Parkinson’s disease (PD). Developing alternative methods to videofluoroscopy swallowing study (VFSS) for the evaluation of dysphagia is a public health necessity. The Swallowing Clinical Assessment Score in Parkinson’s Disease (SCAS-PD) is an alternative and low-cost tool for diagnosis of dysphagia, but had not been properly validated in comparison to the gold-standard method. The objective of this study was to assess the validity and reliability of the SCAS-PD. Methods. SCAS-PD was applied to 31 patients with PD, and VFSS was conducted concurrently. This clinical assessment uses different volumes and viscosities to identify signs of swallowing impairments. For validation purposes, the interclass correlation coefficient and the weighted kappa were calculated. The AUC of the ROC curve, sensitivity, and specificity values for detection of penetration/aspiration (PA) were assessed. Internal consistency was calculated by Cronbach’s alpha. Results. Fifty-one percent of patients were classified with dysphagia. SCAS-PD was differentiated between normal/functional deglutition and dysphagia with AUC 0.97, 95% CI 0.92–1.00, and an optimal cutoff at 19 (sensitivity 100% and specificity 87.5%). The internal consistency was α = 0.91 for the total score. The internal consistency of the SCAS-PD domains was oral phase (α = 0.73), pharyngeal phase (α = 0.86), and signs of PA (α = 0.95). The weighted kappa analysis demonstrated a high rate of concordance at 0.71 (p<0.001) between SCAS-PD and VFSS. Conclusions. SCAS-PD has been shown to have a good concordance with the VFSS. Considering this, SCAS-PD is highly applicable in clinical settings, since it is a simple and low-cost diagnostic tool for detecting dysphagia in PD patients.